2006
DOI: 10.1089/hum.2006.17.1187
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the CYP2B1/Cyclophosphamide Suicide System to Fibroblast Growth Factor Receptors Results in a Potent Antitumoral Response in Pancreatic Cancer Models

Abstract: The CYP2B1/cyclophosphamide (CPA) suicide gene therapy approach has been shown to be highly promising in clinical trials for the treatment of pancreatic cancer. However, delivering the therapeutic gene to a sufficient number of tumor cells able to trigger a complete response remains a challenge. Target-specific delivery of adenovirus to fibroblast growth factor receptors (FGFRs) has been obtained in a variety of tumor models and has been shown to highly increase transduction efficiency. In the present paper we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Consequently, modification to redirect adenoviral tropism to receptors highly expressed in cancer cells might improve tumor transduction and lead to an increased antitumoral effect. Huch et al showed that in a pancreatic cancer model retargeting Ad-CYP2B1/CPA to fibroblast growth factor receptors resulted in a potent antitumoral effect and an increased survival rate, and it increased the potency of the CYP/CPA system [118].…”
Section: Entry Targeting: Vector-mediated Suicide Gene Therapymentioning
confidence: 99%
“…Consequently, modification to redirect adenoviral tropism to receptors highly expressed in cancer cells might improve tumor transduction and lead to an increased antitumoral effect. Huch et al showed that in a pancreatic cancer model retargeting Ad-CYP2B1/CPA to fibroblast growth factor receptors resulted in a potent antitumoral effect and an increased survival rate, and it increased the potency of the CYP/CPA system [118].…”
Section: Entry Targeting: Vector-mediated Suicide Gene Therapymentioning
confidence: 99%
“…Surgical specimens were obtained as formalin-fixed paraffin-embedded tissues as previously indicated (16). Sections (5-mm thick) were submitted to standard deparaffin processing and treated with 10 mmol/L citrate buffer (pH 6.0) for antigen retrieval.…”
Section: Immunohistochemical Assessmentmentioning
confidence: 99%
“…Tumor cell lines (see Supplemental Information) were maintained as described elsewhere (10,14). Human pancreatic duct epithelial (HPDE) cells were maintained as described elsewhere (15).…”
Section: Cell Culturementioning
confidence: 99%
“…Xenografts were generated as described elsewhere (14). Mice were anesthetized, and D-Firefly-Luciferin (Xenogen, Alameda, CA, USA) was administered intraperitoneally (i.p., 16 mg/kg).…”
Section: Bioluminescence and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation